The Importance of Vitamin-D in Androgenic Alopecia and Telogen Effluvium - Gülbahar Saraç; Tuba Tülay Koca (National Scientific Medical Center, 2018)
Aim: Androgenic alopecia (AA) is defined as progressive miniaturization of scarless hair follicle prevailing among both male and female. Telogen effluvium (TE) is the most common hair loss form accompanying systemic diseases. It is aimed to determine the role of vitamine D, the significance of which has been increasing in recent years, in hair loss problem within the scope of this study.  Methods: The patients who applied to Dermatology clinic with the complaint of hair loss and diagnosed androgenic alopecia and telogen effluvium by clinic examination between the years 2015-2016 were included into this study. The age, gender and 25'OHvitamin-D level of the patients were recorded retrospectively. Results: One-hundred eighty seven (N=187) participants (140 female / 47 male) were included in this study. Fifty-eight (N=58) patients (28 female / 30 male) with androgenic alopecia diagnosis formed the first group; 71 patients (65 female / 6 male) with telogen effluvium were formed the second group and 58 healthy volunteers (47 female / 11male) were included in the control group. When Vitamin-D level of first group (AA) was compared with that of the second group (TE) and the control group, there was a statistically significant difference observed (p=0.01/p=0.01 respectively). However, there was no statistically significant difference between the vitamin-D level of second group (TE) and that of the healthy control group (p=0.61). Conclusion: The level of 25'(OH) vit D was found high in androgenic alopecia group than telogen effluvium and controls. Revealing the relationship between vitamin-D level and hair loss might give us the opportunity to come up with new treatment options considering refractory patients.